Combining natural and anthropic atributtes for aquifers contamination potential in southeast of Brazil - Costa, Carlos Wilmer; Lorandi, Reinaldo; Lollo, José Augusto Di [UNESP]; Serikawa, Vagner De Souza (Editora da Universidade Federal de Uberlândia - EDUFU, 2022)
The compromise of surface water resources' quantity and quality, as well as the extensive use of groundwater, exposes aquifers to contamination risks. Considering this, combine natural and manmade influences is a proper strategy for potential aquifer contamination evaluation. This article presents charts of aquifer contamination potential in Rio Claro watershed (251,91km2, in Santa Rita do Passa Quatro, SP) at 1:50,000 scale, taking in account aquifer units, surface geology units, soil and steepness information; operated using multicriteria analysis. The classes “Very high” and “High potential” where the most representative classes of contamination potential in the watershed (performing 46.1% in 1994 and 48.6% in 2014). Obtained contamination potential expressed geological attributes influence in the area. Land use / land cover changes were determinant for higher potential maintenance with time. Adoption of land use / land cover control measures and improvements in tillage management are alternatives for the groundwater protection in this watershed.
Keywords: Groundwater; GIS; Multicriteria analysis; Geo-environmental attributes